Linear and angular head accelerations during heading of a soccer ball - Naunheim, R. S.; Bayly, P. V.; Standeven, J.; Neubauer, J. S.; Lewis, L. M.; Genin, G. M. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: Cognitive deficits observed in professional soccer players may be related to heading of a soccer ball. To assess the severity of a single instance of heading a soccer ball, this study experimentally and theoretically evaluated the linear and angular accelerations experienced by the human head during a frontal heading maneuver. METHODS: Accelerations were measured using a set of three triaxial accelerometers mounted to the head of each of four adult male subjects. These measurements (nine signals) were used to estimate the linear acceleration of the mass center and the angular acceleration of the head. Results were obtained for ball speeds of 9 and 12 m.s(-1) (approximately 20 and 26 mph). A simple mathematical model was derived for comparison. RESULTS: At 9 m.s(-1), peak linear acceleration of the head was 158 +/- 19 m.s(-2) (mean +/- standard deviation) and peak angular acceleration was 1302 +/- 324 rad.s(-2); at 12 m.s(-1), the values were 199 +/- 27 m.s-2 and 1457 +/- 297 rad.s-2, respectively. The initial acceleration pulses lasted approximately 25 ms. Measured head accelerations confirmed laboratory headform measurements reported in the literature and fell within the ranges predicted by the theoretical model. CONCLUSIONS: Linear and angular acceleration levels for a single heading maneuver were well below those thought to be associated with traumatic brain injury, as were computed values of the Gadd Severity Index and the Head Injury Criterion. However, the effect of repeated acceleration at this relatively low level is unknown.